Determinan Initial Return IPO di Indonesia: Pandemi, Pasca-Pandemi dengan Pendekatan Bootstrap - Moh. Alwi; Muliati Muliati; Muhammad Din; Muhammad Ilham Pakawaru (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This study analyzes financial and non-financial factors influencing the initial return of IPO companies listed on the Indonesia Stock Exchange during the pandemic period (2020–2022) and the post-pandemic period (2023–2024).Method - A quantitative approach was employed, utilizing secondary data from IPO prospectuses, IDX publications, and stock prices. The data were analyzed using multiple linear regression with the bootstrap method. Employing a purposive sampling technique, this study obtained a final sample of 131 companies out of a total population of 278 IPO firms.Main Findings - EPS, financial leverage, liquidity, and the percentage of shares offered significantly and positively affect the initial return, while profitability, underwriter reputation, and firm age show no significant effect. Investors tend to respond more strongly to fundamental signals than to underwriter reputation or firm age.Theory and Practical Implications - The findings reinforce Signaling Theory and suggest that issuers should emphasize transparency in EPS, leverage, and liquidity to strengthen investor confidence.Novelty - The novelty of this study lies in its analysis of the determinants of initial return, covering the entire period from the pandemic to the post-pandemic era in Indonesia, while applying the bootstrapping method to address the issue of heteroscedasticity in the data.